2015
DOI: 10.1002/asia.201500415
|View full text |Cite
|
Sign up to set email alerts
|

Iron(III)‐Selective Chelation‐Enhanced Fluorescence Sensing for In Vivo Imaging Applications

Abstract: A "turn-on" pattern Fe(3+) -selective fluorescent sensor was synthesized and characterized that showed high fluorescence discrimination of Fe(3+) over Fe(2+) and other tested ions. With a 62-fold fluorescence enhancement towards Fe(3+) , the probe was employed to detect Fe(3+) in vivo in HeLa cells and Caenorhabditis elegans, and it was also successfully used to elucidate Fe(3+) enrichment and exchange infected by innexin3 (Inx3) in hemichannel-closed Sf9 cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…In contrast, iron supplementation significantly upregulated protein levels of ferritin in worms grown on either E. coli OP50 or S. Typhimurium (Fig 4D and 4H). Next, we used RDN3, a ferric (Fe 3+ )-selective fluorescent sensor [34], to label the ferric form. We found that the ferric foci stained by this dye were merged into ferritin, as detected by immunofluorescence (S6 Fig) . Thus, the ferric foci mainly represent iron in ferritin.…”
Section: Plos Geneticsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, iron supplementation significantly upregulated protein levels of ferritin in worms grown on either E. coli OP50 or S. Typhimurium (Fig 4D and 4H). Next, we used RDN3, a ferric (Fe 3+ )-selective fluorescent sensor [34], to label the ferric form. We found that the ferric foci stained by this dye were merged into ferritin, as detected by immunofluorescence (S6 Fig) . Thus, the ferric foci mainly represent iron in ferritin.…”
Section: Plos Geneticsmentioning
confidence: 99%
“…For detecting fluorescent signals in worms, ftn-1p::pes-10::gfp-his and ftn-2p::pes-10::gfp-his strains were mounted in M9 onto microscope slides. Ferric (Fe 3+ )-selective fluorescent sensor RDN3 were used to stain label the ferric form stored in worms according to the method described previously [34]. The worms were analyzed using a Zeiss Axioskop 2 Plus fluorescence microscope (Carl Zeiss, Jena, Germany).…”
Section: Microscopymentioning
confidence: 99%
“…Hence, detection of Zn II from drinking water is essential. Among various detection procedures, chelation enhanced fluorescence (CHEF) is highly effective, as it provides fluorescence enhancement with or without any spectral shifts after chelation with specific metal ions. Hence the presence of metal ion could be easily detected by naked eye.…”
Section: Introductionmentioning
confidence: 99%
“…N‐terminal‐elongated (Nte) residues of Inx2 and Inx3 can be made by using Bac‐to‐Bac system containing NT‐6His‐TEV to produce reBac‐Nte‐Inxs. At 24‐h post‐infection (PI), hemichannel closes, endogenous phosphate ion accumulates, and Fe 3+ is enriched in reBac‐Nte‐Inx3 (Guo et al., , ; Zhang et al., ).…”
Section: Introductionmentioning
confidence: 99%